Auceps syllabarum: A Digital Analysis of Latin Prose Rhythm. (November 2019) - Keeline, Tom; Kirby, Tyler
Abstract: In this article we describe a series of computer algorithms that generate prose rhythm data for any digitised corpus of Latin texts. Using these algorithms, we present prose rhythm data for most major extant Latin prose authors from Cato the Elder through the second century a.d . Next we offer a new approach to determining the statistical significance of such data. We show that, while only some Latin authors adhere to the Ciceronian rhythmic canon, every Latin author is 'rhythmical' — they just choose different rhythms. Then we give answers to some particular questions based on our data and statistical approach, focusing on Cicero, Sallust, Tacitus and Pliny the Younger. In addition to providing comprehensive new data on Latin prose rhythm, presenting new results based on that data and confirming certain long-standing beliefs, we hope to make a contribution to a discussion of digital and statistical methodology in the study of Latin prose rhythm and in Classics more generally. The Supplementary Material available online (https://doi.org/10.1017/S0075435819000881 ) contains an appendix with tables, data and code. This appendix constitutes a static 'version of record' for the data presented in this article, but we expect to continue to update our code and data; updates can be found in the repository of the Classical Language Toolkit (https://github.com/cltk/cltk ).